A Study on The Speaking Ability of The First Grade Students of SMA Swasta Terakreditasi PGRI Kupang in The Academic Year 2023/2024: English - Banani, Mersi Adince; Isu, Rudolof J.; Sekoni, Rocky P. (Universitas Persatuan Guru 1945 NTT, 2024)
This article entitle A Study on the Speaking Ability of the First Grade Students of SMA Swasta Terakreditasi PGRI Kupang in the Academic Year 2023/2024. This study takes place at the first grade of SMA Swasta Terakreditasi PGRI Kupang. This study formulated as follows. (1). To what extend are the first grade of SMA Swasta Terakreditasi PGRI Kupang able to speak English?. (2). What are the difficulties encountered by the first grade of SMA Swasta Terakreditasi PGRI Kupang in speaking English? The aims of this study are: (1). To know the extend of the first grade of SMA Swasta Terakreditasi PGRI Kupang able to speak English, and (2). To find out the difficulties encountered by the first grade of SMA Swasta Terakreditasi PGRI Kupang in speaking English. In this research, the writer used descriptive method. The ability of the first semester students of English Study Program in the academic year 2023/2024 in a study on the speaking ability were in at good level. It was proved by the students' individual scores which is about 70 to 79 of their score and the students' ability level is about 44% which is higher than the others. It was followed by poor level, fair level and excellent level. Based on the students' item difficulty, it shows that there were four number of items who considered as the difficulty items, namely, item number 3 (80%). 12 (76%), 26 (64%) and 29 (60%). It indicates that some of the students had difficult in doing paraphrasing test which deals with family topic than matching speaking test. In this case, they had speaking limitation in order to express the new words given to them 52.